Étude par simulation à base d’agents des effets des discontinuités intra-urbaines à Delhi sur la dispersion des moustiques Aedes aegypti, vecteurs de la dengue, de la fièvre jaune, du chikungunya et du virus Zika - Somsakun Maneerat; Éric Daudé (Cybergeo)
In order to fight against the transmission of dengue, yellow fever, chikungunya and Zika viruses, significant resources were allocated to the process of restricting the propagation of their main vector, the Aedes aegypti mosquito. Research on this mosquito’s living areas is thus necessary to characterize more precisely the areas that need to be monitored and treated. An alternative to field surveys consists of evaluating the characteristics of these living areas through spatialized models. It is in this context that we developed the simulation model MOMA (Model Of Mosquito Aedes aegypti), an agent-based model which integrates a vast set of biological and behavioural knowledge about the mosquito in a simulation environment based on the needs and constraints specific to Aedes aegypti. In this paper, we present MOMA and a study of the effects of local configurations on the dispersion capacity of mosquito cohorts. The simulations in this study were carried out using data from an urban neighbourhood in the city of Delhi (India). This virtual laboratory, constructed in collaboration with entomologists, thus makes it possible to represent the mosquito’s living areas, which are either restricted or facilitated by spatial amenities conditioning its needs and its capacity of movement during its lifetime.